Molecular and mitochondrial biology of eusocial bees: responses to stress and xenobiotics - Sargent, Chloe (2024)
Bees are one of the most important pollinators and provide substantial economic value via their pollination services. Over recent decades the decline in pollinator diversity and abundance has been of great concern. The cause of these declines has been attributed to a combination of factors including habitat loss, agriculture intensification and pesticide use, climate change, and disease. Hence, it is important to elucidate how these stressors may affect the physiology and molecular biology of bees and thereby help to establish potential stress-biomarkers to monitor and mitigate negative environmental effects. This thesis aims to investigate the effects that environmental stressors and xenobiotics have on mitochondrial function and epigenetic modifications in the eusocial bees, Bombus terrestris and Apis mellifera. Using high-resolution respirometry and tethered flight mills this thesis shows how mitochondrial function and flight performance are affected by chemical stressors. Furthermore, it is demonstrated that bumblebees can be used as effective model organisms for research and development of pharmaceutical drugs. To detect the epigenetic modification, N6-methyladenine (6mA) methylation, in the DNA of bees, the use of techniques including Oxford Nanopore sequencing and a new approach termed the immuno-southern (iSouthern) are also demonstrated.